Analysis of Source and Use of Working Capital In PT. Sido Muncul, Tbk. (Period 2016-2018) - Wahyuni, Menik Tri (Quantitative Economics and Management Studies, 2021)
Working capital is a very important part of the company. Working capital should always be available enough to be able to provide maximum benefits and the company’s operations can continues. Analysis of source and use of working capital is needed for companies to find out the source of funds and how those fund spent.The purpose of this study is to determine the analysis of sources and uses of working capital of PT Sido Muncul,Tbk in Semarang, and to review the policy of uses working capital of PT Sido Muncul, Tbk in Semarang. This study use dercriptive qualitative method. The result of this research indicate that the source of working capital in 2016 to 2018 is quite good. However, in 2017 and 2018 the use of working capital’s company is greater than the source. In 2016 working capital of PT Sido Muncul was increase Rp55.060.000.000. Whereas in 2017 was decrease Rp158.045.000.000 and in 2018 also decreased Rp241.108.000.000. This is due to the high amount of increase in fixed assets by the company. For investment policies, companies tend to use conservative policies, while for working capital expenditure policies companies tend to use aggressive policies.